2020
DOI: 10.1007/s40122-020-00197-x
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Release Dinalbuphine Sebacate Versus Intravenous Patient-Controlled Analgesia with Fentanyl for Postoperative Moderate-to-Severe Pain: A Randomized Controlled Trial

Abstract: Introduction: Post-operative pain control remains unsatisfactory in patients after laparotomy. This study aimed to evaluate the efficacy, safety, and quality of life with a single dose of extended-release dinalbuphine sebacate (ERDS) pre-operatively to intravenous patient-controlled analgesia (PCA) with fentanyl in patients undergoing laparotomy. Methods: This was a prospective, open-label, randomized controlled study. Of 110 randomized patients, 107 completed all assessments. The area under the curve (AUC) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Because ANI scores reflect changes in the nociceptive level with more sensitivity than traditional parameters such as heart rate and blood pressure, we used the ANI to determine the potential impact of DS on perioperative anaesthesia usage [30,31]. Even though DS was administered before surgery, we found no difference in fentanyl usage during surgery between the two groups, which is consistent with previous reports [13][14][15].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Because ANI scores reflect changes in the nociceptive level with more sensitivity than traditional parameters such as heart rate and blood pressure, we used the ANI to determine the potential impact of DS on perioperative anaesthesia usage [30,31]. Even though DS was administered before surgery, we found no difference in fentanyl usage during surgery between the two groups, which is consistent with previous reports [13][14][15].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, a previous phase III study in a population undergoing haemorrhoidectomy demonstrated that the analgesic effect of DS was capable of lasting for about 6 days [12]. The safety and efficacy of DS were also investigated with regard to post-operative pain control of several types of abdominal surgery [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“… 16 Furthermore, a randomized controlled study reported that a single dose of DNS was superior to intravenous PCA with fentanyl in patients who underwent laparotomy. 12 In the present study, the patients received laparotomic staging, debulking, or radical surgery for uterine, ovarian, or cervical cancers. For patients with suspected ovarian cancer, intraoperative frozen section diagnosis was performed during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown benefits of less postoperative analgesic consumption and sufficient efficacy in POP pain intensity management. 12 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…Three previous randomized double-blind placebo-controlled trials have demonstrated that a single preoperative injection of 150 mg SDE provides significant clinical analgesic effects in the management of post-open surgery pain. [11–13] However, the results of this clinical trial did not find any significant additive analgesic effect of SDE compared with the intraoperative MMA only group (parecoxib and propacetamol with or without morphine) for acute pain up to 7 days after laparoscopic cholecystectomy. In comparison to the previous controlled studies, [11–13] there were 2 main differences in our study design.…”
Section: Discussionmentioning
confidence: 79%